2017
DOI: 10.1186/s13287-017-0701-4
|View full text |Cite
|
Sign up to set email alerts
|

Single cell transcriptomics suggest that human adipocyte progenitor cells constitute a homogeneous cell population

Abstract: Regulation of adipose tissue stem cells (ASCs) and adipogenesis impact the development of excess body fat-related metabolic complications. Animal studies have suggested the presence of distinct subtypes of ASCs with different differentiation properties. In addition, ASCs are becoming the biggest source of mesenchymal stem cells used in therapies, which requires deep characterization. Using unbiased single cell transcriptomics we aimed to characterize ASC populations in human subcutaneous white adipose tissue (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 23 publications
5
57
0
Order By: Relevance
“…Further analyses in the same dataset demonstrated that TGFB2 and -3 were most highly expressed in progenitor cells, while TGFB1 was particularly prominent in leukocytes ( Figure S1H). Data at the single-cell level (Acosta et al, 2017) confirmed an enrichment of TGFB3 in human adipocyte precursor cells ( Figure S1I).…”
Section: Expression Of Tgfb Members and Their Receptors In Cells Of Hmentioning
confidence: 58%
See 1 more Smart Citation
“…Further analyses in the same dataset demonstrated that TGFB2 and -3 were most highly expressed in progenitor cells, while TGFB1 was particularly prominent in leukocytes ( Figure S1H). Data at the single-cell level (Acosta et al, 2017) confirmed an enrichment of TGFB3 in human adipocyte precursor cells ( Figure S1I).…”
Section: Expression Of Tgfb Members and Their Receptors In Cells Of Hmentioning
confidence: 58%
“…Analyses of mRNA expression in intact or fractionated human sWAT revealed that the corresponding GF genes were primarily expressed in the SVF and only to a limited degree in mature adipocytes ( Figure S1A). Furthermore, microarray data from fractionated SVFs (Acosta et al, 2017) showed that all GFs were primarily expressed in the adipocyte progenitor (CD45 À / CD34 + /CD31 À ) cell fraction (graphs not shown). These findings were confirmed at the protein level for four of the factors.…”
Section: Tgfb3 Stimulates Adipocyte Precursor Proliferation and Fat Cmentioning
confidence: 99%
“…The primary source of CCL18 is M2 macrophages, but WAT release of CCL18 was highly correlated to classic proinflammatory cytokines as well. This questions the traditional division of macrophages into M1 and M2 phenotype, and rather supports more lately notions of intermediate macrophage states 157 , including metabolically activated macrophages in obesity 111 . CCL18 is known to be involved in development of pulmonary fibrosis 158 , and we hypothesized that potential metabolic effects in adipose tissue may be mediated by development of fibrosis, i.e.…”
Section: Study Specific Aspectsmentioning
confidence: 69%
“…Quantitative PCR for each cDNA was conducted with Taqman probes using iTaq Universal Probe Supermix (BioRad, Hercules, CA). Microarray data of different resident cells in human subcutaneous adipose tissue were generated as described [23]. …”
Section: Methodsmentioning
confidence: 99%
“…Microarray data of different resident cells in human subcutaneous adipose tissue were generated as described. 23…”
Section: Quantitative Rt-pcr and Gene Expression Analysesmentioning
confidence: 99%